2023
DOI: 10.2489/jswc.2023.00064
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon and nitrogen storage estimated with the root-zone enrichment method under conventional and conservation land management across North Carolina

Abstract: Agriculture is a globally dominating land use, so efforts to restore soil organic carbon (C) and nitrogen (N) lost through historical degradation could have enormous benefits to production and the environment, particularly by storing an organic reserve of nutrients in soil and avoiding the return of a small portion of biologically cycling C to the atmosphere. Estimates of soil organic C and N storage from conservation agricultural management are still limited when considered in proportion to the large diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 43 publications
7
29
0
Order By: Relevance
“…The only orthogonal contrast with statistical significance was broadly between conservation land uses (grassland and woodland) and cropland (conventional‐till and no‐till) ( p < 0.001). These associations illustrate that the factors controlling antecedent conditions of the stock of total soil N also likely controlled root‐zone enrichment of STBA, such as climatic conditions and soil texture (Franzluebbers, 2023).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The only orthogonal contrast with statistical significance was broadly between conservation land uses (grassland and woodland) and cropland (conventional‐till and no‐till) ( p < 0.001). These associations illustrate that the factors controlling antecedent conditions of the stock of total soil N also likely controlled root‐zone enrichment of STBA, such as climatic conditions and soil texture (Franzluebbers, 2023).…”
Section: Resultsmentioning
confidence: 98%
“…The only orthogonal contrast with statistical significance was broadly between conservation land uses (grassland and woodland) and cropland (conventional-till and no-till) (p < 0.001). These associations illustrate that the factors controlling antecedent conditions of the stock of total soil N also likely controlled root-zone enrichment of STBA, such as climatic conditions and soil texture (Franzluebbers, 2023). With total soil N as the primary variable affecting rootzone enrichment of STBA and assessing variations within each land use separately, sand concentration at 0-to 30-cm depth was also an important covariate in some land use categories.…”
Section: Land Use Effects On Stbamentioning
confidence: 85%
“…Taken as a whole, the papers presented in this special issue address this call to action. The research papers share new findings related to management approaches to increase soil organic C (Kutos et al 2023;Franzluebbers 2023) and decrease N leaching (Shrestha et al 2023) in major agricultural land management systems. New knowledge about the importance of the soil microbiome points the way forward to improved systems in the future (Bell et al 2023), and the findings of Watts et al (2023) indicate that co-benefits of GHG mitigaton may be associated with conservation practices implemented for other purposes and that additional research in this area is needed.…”
Section: Current Understanding and Toolsmentioning
confidence: 95%
“…Analysis of land use impacts on C and N from research stations across North Carolina revealed that the root zone enrichment approach allowed separation of management and pedogenisis effects (Franzluebbers 2023). Variations in soil type and management within a region were equally influential in determining soil C and N contents.…”
Section: Current Understanding and Toolsmentioning
confidence: 99%
See 1 more Smart Citation